Microstructure and mechanical property of B4C–SiC–CrB2 composites fabricated via reactive hot pressing. Issue 18 (15th December 2020) - Wang, Shuai; Deng, Yangyang; Yang, Mingsheng; Wang, Luyao; Li, Huaiqian; Xing, Pengfei
Abstract: Dense B4 C–SiC–CrB2 ternary composites were fabricated via reactive hot pressing with B4 C and chromic silicides (84 wt% CrSi2 +16 wt% CrSi) as raw materials. The effects of chromic silicides on the densification, phase components, microstructure and performance of the prepared composites were investigated. The reaction mechanism and toughening mechanism were also studied. The results indicated that the chromic silicides were the reactive sintering aids which reacted with B4 C and C to introduce CrB2 and SiC in the matrix in situ. Partial B4 C, CrB2 and SiC formed the eutectic liquid phase, which enhanced the densification of B4 C. The addition of chromic silicides enhanced the densification and fracture toughness while reduced the hardness. The good comprehensive performances of 435 MPa flexural strength, 4.09 MPa m 1/2 fracture toughness and 33.11 GPa hardness were obtained in the composites fabricated with 10 wt% chromic silicides. The higher addition amounts of chromic silicides resulted in the larger-size SiC, which reduced the flexural strength. The transgranular fracture of SiC and partial CrB2, the existing phenomena such as microcracks, crack branching and crack deflection could cumulatively improve the fracture toughness of the materials.